Феохромоцитома як компонент синдому Гіппеля-Ландау в практиці ендокринолога: проблеми діагностики на прикладі клінічного спостереження - Глоба, Є. В.; Зелінська, Н. Б. (Clinical Endocrinology and Endocrine Surgery, 2010)
In the article clinical case of rare disease — Von Hippel-Lindau syndrome is given. It was established after many years from the moment of the beginning of the first syndrome component — pheochromocytoma.